Do demographic and socio-economic factors predict Sense of Coherence among university students? - Guglielmo Bonaccorsi; Patrizio Zanobini; Claudia Cosma; Primo Buscemi; Sonia Paoli; Vieri Lastrucci; Valerio Ferro Allodola; Andrea Moscadelli; Orkan Okan; Kevin Dadaczynski; Chiara Lorini (Istituto Superiore di Sanità, 2023)
Introduction. The COVID-19 pandemic and related containment measures have been threatful for psychological well-being, particularly for young people such as university students. Sense of Coherence (SoC) can help in coping with stressful and anxiety-provoking situations. Aim. The aim of this study is to describe the levels of SoC and to investigate the socioeconomic, and demographic predictors in a sample of students attending Florence University, in the timespan between August, 17th and October, 3rd 2020. Method and results. The cross-sectional online survey was completed by 2,996 students. Higher levels of SoC have been found among males and for respondents reporting a better socioeconomic condition. Regarding the dimensions of SoC, lower levels were reported for comprehensibility and manageability, higher for meaningfulness. Conclusions. These results reinforce the need to plan and implement health promotion interventions aimed to support and sustain university students in general and specifically those at higher risk of low level of SoC.